Importing Inputs for Climate Change Mitigation : The Case of Agricultural Productivity - Garcia-Verdu, Rodrigo (IMF Working Papers; Working Paper, 2019)
This paper estimates agricultural total factor productivity (TFP) in 162 countries between 1991 and 2015 and aims to understand sources of cross-country variations in agricultural TFP levels and its growth rates. Two factors affecting agricultural TFP are analyzed in detail - imported intermediate inputs and climate. We first show that these two factors are independently important in explaining agricultural TFP - imported inputs raise agricultural TFP; and higher temperatures and rainfall shortages impede TFP growth, particularly in low-income countries (LICs). We also provide a new evidence that, within LICs, those with a higher import component of intermediate inputs seem to be more shielded from the negative impacts of weather shocks.